Emotional Intelligence with Learning Achievements Reviewed from Islamic Education - Nur Aisyiah Yusri; Mariah Kibtiyah; Thoat Hamim (International Journal of Islamic Educational Psychology, 2020)
One of the psychological aspects that determine the quality of learning outcomes, it closely relates emotional factors to emotional intelligence. Emotional intelligence is one of the knowledge models developed in psychology based on various arguments and scientific findings from neuroscience studies and analysis. This article discusses the relationship between emotional intelligence and student achievement. The sample used was 248 high school students in Padang city, and the data analysis technique was Pearson's product-moment correlation. This research study instrument was the emotional intelligence scale, while they obtained student learning achievement from the report card scores in the odd semester of the 2019-2020 school year. The results showed that there was a significant interrelationship between emotional intelligence and student achievement.